2022
DOI: 10.2116/analsci.21p283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrophilic/hydrophobic blocks ratio of PEG-b-PLGA on emission intensity and stability of over-1000 nm near-infrared (NIR-II) fluorescence dye-loaded polymeric micellar nanoparticles

Abstract: Polymeric micellar nanoparticles (PNPs) composed of the amphiphilic block copolymer formed from hydrophilic and hydrophobic blocks and over-thousand-nanometer (OTN) near-infrared (NIR) fluorescent dye are promising fluorophores for dynamic imaging of deep tissue. In this study, we examined the effect of the ratio of hydrophilic/hydrophobic blocks of a block copolymer, poly(ethylene glycol) (PEG)-b-poly(lactide-co-glycolide) (PLGA), on the properties of OTN-PNPs encapsulating IR-1061. OTN-PNPs with a higher mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…PEG- b -PLLA and PEG- b -PDLLA co-polymers with the same chain lengths (molecular weights; PEG Mw: 2000, PLA Mw: 5000) were used to avoid the potential bias effects of the polymer molecular weights on the encapsulation properties of IR-1061 shown in previous investigations. 33 The stability of IR-1061 in micelles was determined by comparing absorption ( Fig. 3 and 4 ), OTN-NIR fluorescence ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEG- b -PLLA and PEG- b -PDLLA co-polymers with the same chain lengths (molecular weights; PEG Mw: 2000, PLA Mw: 5000) were used to avoid the potential bias effects of the polymer molecular weights on the encapsulation properties of IR-1061 shown in previous investigations. 33 The stability of IR-1061 in micelles was determined by comparing absorption ( Fig. 3 and 4 ), OTN-NIR fluorescence ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 Currently, there is a wide variety of OTN-NIR uorescent probes 6 including quantum dots, [7][8][9][10] single-walled carbon nanotubes, [11][12][13][14][15][16][17][18][19][20] lanthanide-doped ceramic nanoparticles, 3,[21][22][23] and organic molecular dyes. [24][25][26][27][28][29][30][31][32][33][34] Compared to inorganic nanoparticles, organic molecular dyes show great potential as probes with low toxicity and low bioaccumulation. 25 IR-1061, a widely used OTN-NIR uorescent dye, has hydrophobic and cationic (polarized) backbones in its molecular structure and a nonpolar counter ion, BF 4 À , that can suppress vibration quenching.…”
Section: Introductionmentioning
confidence: 99%
“…For IR-1061-encapsulated micelles with shells composed of PEG, a biocompatible hydrophilic polymer, the effect of the molecular weight of a PLGA core polymer, which has a high affinity for the dye, was investigated [110]. In this study, the fluorescence performances of micellar nanoparticles encapsulating IR-1061 in PEG-b-PLGA with PLGA molecular weights of 1000, 2000, and 5000, and a PEG molecular weight of 2000 were compared.…”
Section: Effect Of the Molecular Weight Of The Hydrophobic Core On Fl...mentioning
confidence: 99%
“…Within this range of PLGA molecular weights (i.e., 1000-5000), the higher the molecular weight of the PLGA core, the higher the dye encapsulation efficiency and fluorescence intensity. Their absorption spectra showed that IR-1061 encapsulated in high-molecular-weight PLGA core was less affected by water molecules with a large phonon energy of polar vibration of hydroxyl bonding [53] in the dispersant [110]. The IR-1061-encapsulated PEG-b-PLGA micelles were highly stable in both in vitro (PBS containing albumin) and in vivo (in the circulating blood of mice) environments, as evidenced by the increase in the molecular weight of PLGA constituting the micelle core [110].…”
Section: Effect Of the Molecular Weight Of The Hydrophobic Core On Fl...mentioning
confidence: 99%
See 1 more Smart Citation